Does Reaching the Statute of Limitations Affect the Recidivist Behavior of Environmental Aggressors in Brazil? - Uhr, Daniel de Abreu Pereira (Journal of quantitative criminology, 2023)
Objectives This study examines the role of law enforcement procedures for environmental offenses. We test whether reaching the statute of limitations is associated with the recidivism of offenses against the flora in Brazil. Methods We analyze the universe of infractions issued by Brazil’s Federal Environmental Agency from 2000 to 2010 using survival analysis and reweighting methods. Results Findings indicate that reaching the statute of limitations in administrative procedures increases the risk of recidivism for individuals by 188% and firms by 34%. Conclusion Ineffective sentencing practices stimulate repeated offenses against the environment and have significant consequences for environmental degradation in Brazil, a country that is central for actions to mitigate global environmental change.